Effect of ozone treatment on the microstructure, chemical composition and sensory quality of apple fruits - Juhnevica-Radenkova, Karina; Radenkovs, Vitalijs; Kundzins, Karlis; Seglina, Dalija (SAGE Publications Inc., 2019)
The aim of this study was to assess the effect of O3 treatment on the quality of different cultivars of apples (Malus domestica Borkh.). Apples were stored for six months at different concentrations of ozone. During the research, minor differences between ozone-treated and control fruits were found in terms of cell integrity and epicuticular wax structure. Ozone application for apple treatment could accelerate the natural ageing of the waxes found on the surface of apples, thereby reducing the thickness of the waxes. The rate of degradation for the epicuticular wax was found to be cultivar dependent. After six months of storage, the ozonation process prevented the decay of ‘Iedzenu’, ‘Auksis’ and ‘Belorusskoje Malinovoje’ apple cultivars, but it accelerated damage in the ‘Gita’ apple cultivar. A positive impact of ozone during long-term storage was found regarding flesh firmness of ‘Iedzenu’ apple cultivar samples subjected to O3 exposure at concentrations of 0.8 ppm and 3.0 ppm. In other cultivars of apples, significant differences between ozonation and cold storage (control) were not found. In general, ozone treatment has a potential to be applied in order to maintain the sensory quality and biologically active compound level in apples during six-month storage; however, the degree of effectiveness depends both on the cultivar and on the concentration of ozone.
The author(s) disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: This research commissioned by Agricultural services co-operative society ‘AUGL¸ NAMS’ has been conducted within framework ‘The research of fruit storage technologies’ funded by State program ‘Competence Centre for Food in Latvia’.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Apple treatment; microstructure; postharvest storage; quality; sensory evaluation